Ramifications of variability in sex hormone-binding globulin measurement by different immunoassays on the calculation of free testosterone. (January 2020) - Adaway, Joanne; Keevil, Brian; Miller, Annmarie; Monaghan, Phillip J; Merrett, Nicola; Owen, Laura
Objective: Sex hormone-binding globulin (SHBG) is a glycoprotein which binds hormones such as testosterone. Around 97% of circulating testosterone is bound to SHBG or albumin and is therefore biologically unavailable; 2–3% of testosterone is free. Free testosterone is very technically challenging to quantify; in order to circumvent this problem, equations using testosterone and SHBG are used to estimate free testosterone. We decided to determine the effect of using different SHBG immunoassays on calculated free testosterone results. Design: Anonymized surplus serum samples were analysed for SHBG on four different immunoassay platforms (Abbott Architect, Roche, Beckman and Siemens). The SHBG results were used to generate a Vermeulen calculated free testosterone. Results: Beckman Access and Siemens Centaur both gave results close to the overall mean. Roche gave the highest SHBG concentrations with Abbott Architect producing the lowest results. Abbott Architect gave the highest calculated free testosterone results, followed by Beckman. Roche gave the lowest results. Sixty-five per cent of male samples had low calculated free testosterone and 27.5% of the females had high calculated free testosterone using the SHBG from the Abbott assay compared with 69% low male calculated free testosterone and 20% high female calculated free testosterone with the Roche assay. Conclusion: Our results have shown significant differences in SHBG results produced by different analysers and subsequently the calculated free testosterone, which may affect result interpretation if method-specific reference ranges for calculated free testosterone are not used. Care should be taken to ensure reference ranges are appropriate for the analyser used to avoid misdiagnosis of hypo or hyperandrogenism, and ensure patients get the most appropriate treatment.